The Influence Of Application Quality And Service Quality On Shopee Customer Satisfaction In Bogor - Mashadi, Mashadi; Khoir, Ahmad Din; Gendalasari, Gen Gen (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to determine: (1) the effect of Application Quality on Shopee Customer Satisfaction in Bogor, (2) the effect of Service Quality on Shopee Customer Satisfaction in Bogor, and (3) The Effect of Application Quality and Service Quality together on Shopee Customer Satisfaction in Bogor. The sample used in this study was 385 samples of Bogor city residents who had shopped or used Shopee. The method used in this research is descriptive quantitative, where theoretical testing is carried out by measuring the research variables numerically and analyzing the data. In this study using primary data obtained directly from respondents who will be collected through a questionnaire. And using SPSS as a tool to solve problems. The questionnaire in this study uses a Likert scale as a measurement scale for research instruments. Based on the descriptive results on each variable, it shows that the independent variables Application Quality (X1) and Service Quality (X2) have a positive and significant effect on the dependent variable Customer Satisfaction (Y). This can be seen from the results of the analysis of the testing of each variable X and Y, both partial testing (t test) and simultaneous testing (f test). Keywords: Application Quality, Service Quality, Customer Satisfaction, Shopee.